The sellout - Beatty, Paul (Oneworld, 2017)
"Raised in the "agrarian ghetto" of Dickens--improbably smack in the middle of downtown L.A.--the narrator of The Sellout resigned himself to the fate of all other middle-class Californians: "to die in the same bedroom you'd grown up in, looking up at the crack in the stucco ceiling that had been there since '68 quake." Raised by a single father, a controversial sociologist at Riverside Community College, he spent his childhood as the subject in psychological studies, classic experiments revised to include a racially-charged twist. He also grew up believing this pioneering work might result in a memoir that would solve their financial woes. But when his father is killed in a shoot out with the police, he realizes there never was a memoir. All that's left is the bill for a drive-thru funeral and some maudlin what-ifs. Fuelled by this injustice and the general disrepair of his down-trodden hometown, he sets out to right another wrong: Dickens has literally been removed from the map to save California further embarrassment. Enlisting the help of the town's most famous resident--the last surviving Little Rascal, Hominy Jenkins, our narrator initiates a course of action--one that includes reinstating slavery and segregating the local high school--destined to bring national attention. These outrageous events land him with a law suit heard by the Supreme Court, the latest in a series of cases revolving around the thorny issue of race in America. The Sellout showcases a comic genius at the top of his game. It challenges the most sacred tenets of the U.S. Constitution, urban life, the civil rights movement, the father-son relationship, and the holy grail of racial equality--the black Chinese restaurant"--